2000
DOI: 10.1111/j.1728-4457.2000.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Crime, Gender, and Society in India: Insights from Homicide Data

Abstract: This study presents an analysis of inter-district variations in murder rates in India in 1981. Three significant patterns emerge. First, murder rates in India bear no significant relation with urbanization or poverty. Second, there is a negative association between literacy and criminal violence. Third, murder rates in India are highly correlated with the female-male ratio in the population: districts with higher female-male ratios have lower murder rates. Alternative hypotheses about the causal relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(92 citation statements)
references
References 13 publications
3
89
0
Order By: Relevance
“…A popular explanation for violence (see Glossary) centers on male-biased sex ratios. Paradigmatic is the concern of heightened violence in both India and China in response to growing numbers of extra men (in China termed 'bare branches') that result from son preference and daughterbiased abortion, infanticide, and neglect [1][2][3][4]. Given that men are typically more prone to engage in violent competition than are women [5], the inference is that more men will necessarily lead to more violence.…”
mentioning
confidence: 99%
“…A popular explanation for violence (see Glossary) centers on male-biased sex ratios. Paradigmatic is the concern of heightened violence in both India and China in response to growing numbers of extra men (in China termed 'bare branches') that result from son preference and daughterbiased abortion, infanticide, and neglect [1][2][3][4]. Given that men are typically more prone to engage in violent competition than are women [5], the inference is that more men will necessarily lead to more violence.…”
mentioning
confidence: 99%
“…Further, the size of the coefªcient of the female-male ratio is quite large." 104 We updated the above analyses by using the 1991 census data and the most recent murder rate available (1997) and found the same strong relationship, yielding p Յ .07. This is prima facie evidence that this linkage has persisted in India through the late 1990s.…”
mentioning
confidence: 99%
“…For example, Miguel et al (2004) reported that in poor areas of Tanzania after an extreme rainfall, which resulted in large income drops, crime rates were increased. It is also evident that current and past economic crises increase the possibility of civil conflict and normlessness in African countries (Dreze and Khera, 2000;Miguel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%